2014
DOI: 10.1088/0029-5515/54/4/043009
|View full text |Cite
|
Sign up to set email alerts
|

Core intrinsic rotation behaviour in ASDEX Upgrade ohmic L-mode plasmas

Abstract: Abstract. The ASDEX Upgrade intrinsic rotation database has been expanded to include a large number of measurements from Ohmic L-mode discharges covering a wide range of plasma densities, currents, and magnetic fields. This database was then used to study the rotation behavior across the transition from linear to saturated Ohmic confinement (LOC/SOC). At low collisionailty the plasma is in the LOC regime and the toroidal rotation profile is in the co-current direction. As the collisionality is increased and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
97
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(118 citation statements)
references
References 43 publications
21
97
0
Order By: Relevance
“…In these works, no clear ITG to TEM transition appears responsible, but rather, more subtle changes in the turbulence correlate with the rotation and particle transport changes. The current work presented here is consistent with these findings [48,18,47,20].…”
Section: Search For Itg/tem Transition Using Nonlinear Gyrokinetic Sisupporting
confidence: 92%
See 1 more Smart Citation
“…In these works, no clear ITG to TEM transition appears responsible, but rather, more subtle changes in the turbulence correlate with the rotation and particle transport changes. The current work presented here is consistent with these findings [48,18,47,20].…”
Section: Search For Itg/tem Transition Using Nonlinear Gyrokinetic Sisupporting
confidence: 92%
“…The nonlinear gyrokinetic analysis of C-Mod plasmas presented here suggests that a clear transition from ITG to TEM does not accompany changes in particle transport and rotation profiles as previously reported on ASDEX-Upgrade [22]. We note that the relationship between changes in the the toroidal rotation and ITG to TEM transition has also been studied recently in Ohmic plasmas and auxiliary heated plasmas at Alcator C-Mod [47] and ASDEX-Upgrade [48,18,20]. In these works, no clear ITG to TEM transition appears responsible, but rather, more subtle changes in the turbulence correlate with the rotation and particle transport changes.…”
Section: Search For Itg/tem Transition Using Nonlinear Gyrokinetic Sisupporting
confidence: 79%
“…11,12 It has been suggested that a unifying hypothesis for these changes is a change in the underlying turbulence from dominant trapped electron mode (TEM) to ion temperature gradient (ITG) across the LOC/SOC transition, 11,12 which will be a continuous transition in terms of their relative amplitudes, not discrete, in reality. There is counter evidence from C-Mod 13 and from ASDEX Upgrade, 14 suggesting that the LOC/SOC transition occurs without a change in turbulence from TEM to ITG. It is also noteworthy that we do not understand clearly all these changes are coupled together.…”
Section: Introductionmentioning
confidence: 98%
“…Although rotation reversal occurs robustly with the LOC/SOC transition in C-Mod, 15 it has been also observed that these two phenomena are not correlated in Tore-Supra 16 and ASDEX-Upgrade. 14,17 These conflicting observations motivated the current work. In addition to studying the physics of the LOC/SOC transition, validation of gyrokinetic codes in a variety of plasmas is of interest.…”
Section: Introductionmentioning
confidence: 98%
“…In helium main-ion plasmas on DIII-D the radial location of the helium velocity hollowing was seen to be dependent on the deposition location of the electron heating [10,11], which ties the reversal phenomenon to the energy flux. Variations of the rotation gradient with changes of the local density gradient have been also been observed [12] indicating the need for local profile investigation to organize the observations. Investigations into the type of linearly unstable turbulence between ion and electron modes that correlate with the observations have been explored [12][13][14], indicating that other processes beyond the dominant turbulence mode, such as the collisionality scaling of non-Maxwellian equilibria [15], are required to explain the wide range of observed phenomenology.…”
mentioning
confidence: 96%